ISLAMIC EDUCATION DISCOURSE TO FORM STUDENT MORALS AT MADRASA - Mansir, Firman (Idaarah: Jurnal Manajemen Pendidikan, 2021)
Abstract: Islamic Education Discourse to Form Student Morals at Madrasa The development of modern technology has an impact on the learning process in madrasa. So, there are many new obstacles that must be turned into excellent opportunities, to be taken into a positive as well as possible. Especially in the development of strong and tough student morals. This study describes Islamic Education (PAI) as part of aqeedah morals learning which is able to shape students’ morals and provide convenience in understanding the material provided by PAI teachers in madrasah. The development of modern technology has an impact on the learning process in madrasa so that many new obstacles must be turned into excellent opportunities to be taken into a positive as well as possible, especially in the development of solid and robust student morals. This type of research is qualitative. The data analysis technique uses an in-depth analysis of the literature according to the source of the data obtained. Meanwhile, the approach used is a pedagogic approach, in order to know the process of forming students’ morals through Islamic Religious Education, by looking at the learning outcomes of aqeedah morals. The result is that students have good morals in their interactions with each other in madrasa. Thus, learning Islamic Religious Education is expected to be able to shape students’ morals with various materials that are loaded with moral values in accordance with the learning objectives. Abstrak: Wacana Pendidikan Islam untuk Membentuk Akhlak Siswa di Madrasah Perkembangan teknologi modern yang terjadi berdampak pada proses pembelajaran di madrasah, sehingga hal ini banyaknya rintangan baru yang harus diubah menjadi peluang yang sangat baik untuk diambil menjadi sebuah positif dengan sebaik-baiknya, khususnya dalam sebuah pengembangan akhlak siswa yang kuat dan tangguh. Penelitian ini bertujuan menjelaskan tentang Pendidikan Agama Islam (PAI) sebagai bagian dari pembelajaran Akidah Akhlak yang mampu membentuk akhlak siswa dan memberikan kemudahan dalam memahami materi yang diberikan oleh guru PAI di madrasah. Jenis penelitian ini adalah kualitatif. Teknik analisis data menggunakan analisis literatur secara mendalam sesuai dengan sumber data yang diperoleh. Sementara itu pendekatan yang digunakan yaitu pendekatan pedagogik, dalam rangka mengetahui proses pembentukan akhlak siswa melalui Pendidikan Agama Islam, dengan melihat hasil pembelajaran Akidah Akhlak. Hasilnya adalah peserta didik memiliki akhlak yang baik dalam interaksinya antar sesama di madrasah. Dengan demikian, pembelajaran Pendidikan Agama Islam diharapkan mampu membentuk akhlak siswa dengan berbagai materi yang sarat dengan nilai-nilai moral yang sesuai dengan tujuan pembelajaran tersebut.